Evaluation of continuous arrhythmia monitoring using an implantable loop recorder in heart failure patients with a reduced ejection fraction: The LINQ2-HF trial rationale and protocol - Ryo Tateishi; Shinsuke Miyazaki; Kazuya Yamao; Miho Negishi; Masaki Honda; Mari Omori; Yoshinori Kanno; Iwanari Kawamura; Yuji Matsuda; Yosuke Yamakami; Kentaro Goto; Kensuke Hirasawa; et al. (PLoS ONE, 2025)
Introduction Heart failure with a reduced ejection fraction (HFrEF) is a common and serious condition often associated with atrial fibrillation (AF) and ventricular arrhythmias, leading to poor outcomes such as rehospitalizations and death. Detecting asymptomatic arrhythmias remains challenging, as traditional monitoring methods like 12-lead electrocardiograms (ECGs) or Holter ECGs are insufficient for continuous surveillance. This study aims to evaluate the utility of continuous arrhythmia monitoring using an implantable loop recorder (ILR) to detect asymptomatic arrhythmias in HFrEF patients, particularly for AF and ventricular tachycardia (VT). Methods and analysis This is a single-center, non-randomized exploratory study. Thirty-five patients with HFrEF (LVEF ≤ 40%) and no history of AF will receive ILR implants. Primary endpoints include the detection of new-onset AF lasting at least 6 minutes and sustained or non-sustained VT. Secondary endpoints include the identification of bradycardia, pauses, and other arrhythmias, along with cardiovascular outcomes such as death and hospitalization. Additionally, secondary endpoints will include arrhythmia treatments, including anticoagulation therapy, catheter ablation, and implant of therapy devices. Data will be collected via remote monitoring through the Medtronic CareLink system, with event rates estimated using Kaplan-Meier methods. Data collection will span three years, with analyses conducted in the first and third years. Conclusion The LINQ2-HF trial is designed to detect new-onset AF and VT in HFrEF patients using ILR, with the aim of informing future strategies for arrhythmia management in this population. Name of the registry Japan Registry of Clinical Trials (jRCT). Trial registry number jRCTs032240593 Registration data https://jrct.niph.go.jp/en-latest-detail/jRCTs032240593